Retrofit of palm oil refinery to improve energy consumption and reduce fouling costs - Abdul Manan, Zainuddin; Mohd Yusof, Feruz (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1994)

(untitled)
This paper presents the results of a detailed process integration retrofit study done on a palm oil refinery. The study, which is based on pinch technology is aimed at optimizing the energy consumption and recovering losses from the process streams of the existing plant. Bulk of the losses can be attributed to suboptimal heat recovery network structure and heat exchanger fouling effects. Previous pinch-based studies on fouling costs reductions were focused on grassroot designs. Retrofit studies reported for palm oil refineries were slightly different in approach and did not take into account of the effects of heat exchanger fouling. The presents study demonstrates that notwithstanding the existing integration scheme employed in the refinery, energy savings of 71% in hot utility and 52% in cold utility with payback period of less than 2 years is possible. The proposed scheme eliminates the need for routine maintenance downtime dedicated for cleaning of fouled exchangers. As a result, energy consumption is further improved and productivity increased.